THE POTENTIAL OF ACADEMIC ENTREPRENEURSHIP: A CHANCE FOR THE DEVELOPMENT OF THE SME SECTOR - Checinska Kopiec, Agnieszka; Ochoa Siguencia, Luis; Grodek Szostak, Zofia (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
Globalization, social and economic progress are associated with such notions as: entrepreneurship, innovation and competitiveness. Both programmes and activities of states and international communities aim to improve the quality of life on a local and global scale by, e.g. reducing unemployment and supporting and increasing the competitiveness of entrepreneurs. The aim of the paper is to show the impact of selected features of tourism-related businesses at the level of their innovation. The paper presents the conditions that must be met in order to develop academic entrepreneurship in Polish universities. Legal conditions, forms of cooperation between universities and business, creation and commercialization of knowledge as well as shaping entrepreneurial attitudes were analysed.